Determinants Affecting Systematic Risk in Pakistan’s Oil and Gas Sector - Muhammad Shoaib Hassan; Gul Mehak; Waqas Mehmood (Audit and Accounting Review, 2025)
The current study aimed to investigate the effect of different determinants on systematic risk in Pakistan’s oil and gas sector. In this study, the data of six systematic risk determinants, namely liquidity, firm size, operating efficiency, profitability, growth, and leverage, was collected from Pakistan Stock Exchange (PSX). Moreover, the firm’s monthly stock return and Karachi Stock Exchange (KSE) 100 index return data for the period of 2018-2022 was obtained from the website of ZHV Securities. Random effect regression analysis was performed to test hypothesis based on the Hausman test to validate the absence of multicollinearity, heteroskedasticity, and serial autocorrelation. Regression results showed that liquidity, profitability, operating efficiency, and leverage had a negative and significant effect. On the other hand, size and growth had a negative but insignificant effect on systematic risk regarding oil and gas companies in Pakistan. The obtained results were consistent with the existing literature and Capital Market Theory (CMT) and Capital Asset Pricing Model (CAPM). Policymakers are recommended to consider implementing measures in order to improve access to finance for companies in the sector, improve operational efficiency, and diversify sources of financing. Furthermore, the researchers are recommended to conduct comparative studies between different sectors to provide more valuable insights considering other determinants as per their country, industry, and sector dynamics.